From a source of weakness to a tower of strength? The changing German labour market - Alexander Herzog-Stein; Fabian Lindner; Simon Sturn; Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
Despite the biggest economic slump in Germany since the Second World War, employment did not decrease. In other European countries, which have even been hit less hard, employment started to decrease significantly. This 'employment miracle' is a result of the high internal flexibility of the German labour market, which resulted in a strong reduction of average working time in the downturn, and labour-hoarding by employers. Cyclical working time reduction saved some 1.1 million jobs, labour hoarding another 2 million. Working hours were reduced via short-time working schemes, working time accounts, and variations in working time at the company level. As these measures had nothing to do with the labour market reforms in the years before the crisis, there is also no direct impact of these reforms on the employment miracle. Also wage moderation, which has been fuelled by these labour market reforms, had no positive impact on the overall labour market performance of Germany. – – Trotz der größten Wirtschaftskrise nach dem 2. Weltkrieg ist die Beschäftigung in Deutschland nicht gefallen. In anderen europäischen Ländern, die sogar weniger von der Wirtschaftskrise betroffen waren, ist die Beschäftigung stark gesunken. Dieses "Arbeitsmarktwunder" erklärt sich durch die schnelle Reduzierung der Arbeitszeit ("interne Flexibilität") und das Horten von Arbeitskräften durch die Hinnahme einer geringeren Produktivität. Die Reduzierung der Arbeitszeit hat etwa 1,1 Millionen Arbeitsplätze gerettet, das Arbeitskräftehorten an die 2 Millionen. Die Arbeitszeit wurde vor allem mit den Instrumenten Kurzarbeit, Arbeitszeitkonten und der Veränderung der betrieblichen Regelarbeitszeit erreicht. All diese Instrumente waren aber nicht Teil der Arbeitsmarktreformen Hartz I-IV. Somit können die Reformen den Arbeitsmarkterfolg in der Großen Rezession nicht erklären. Auch die Lohnmoderation der letzten Jahre, die durch die Reformen verstärkt wurde, hat kaum geholfen. Sie hat im Konjunkturzyklus vor der Krise die Beschäftigungsentwicklung sogar belastet.
urn:nbn:de:101:1-201202274268
Keywords: 330; Wirtschaftskrise; Arbeitsmarktflexibilität; Beschäftigungseffekt; Internationaler Wettbewerb; Wirtschaftswachstum; Deutschland